HUBUNGAN KONDISI RUMAH PENDERITA TB PARU DENGAN KEBERHASILAN PENGOBATAN TB PARU DI RSUD DR.RM.PRATOMO BAGANSIAPIAPI - Alini Alini (Universitas Pahlawan, 2017)
Tuberculosis is a contagious disease caused by TB (mycobacterium tuberculosis), a house that does not meet the health requirements is one of the risk factors of pulmonary tuberculosis transmission. This study aims to determine the relationship of home conditions with the success of TB treatment of Lung in RSUD dr.RM.Pratomo Bagansiapiapi Year 2016. This research is analytic by using Cross Sectional research approach. Population and sample in this research is all patient of Pulmonary Tuberculosis who undergo Pulmonary TB treatment for 6 months Year 2016 counted 50 people with sampling total sampling technique. Data collection through questionnaires. Data processing using univariate and bivariate analysis. The result of this research shows that most of respondent have house condition not fulfill health requirement that is counted 34 people (68,0%), most of respondent not succeed in treatment of Pulmonary TB that is counted 32 person (64,0%). Chi-square test results obtained that there is a significant relationship between the condition of the house with the success of treatment of pulmonary tuberculosis in RSUD dr.RM.Pratomo Bagansiapiapi Rokan Hilir District in 2017 with p value 0,000. With this research is expected to the respondents pay attention and maintain healthy home conditions in order to support the healing process